The Nature of the Electron (Global Journal of Science Frontier Research, 2025)
Unity is defined as matter or a system with its maximum energy limit In an atom unity electrons are attracting while energy sharing Out of the unity electrons are kinetically repelling while excess-energy releasing gradually The concept of a specific electric charge is a misconception also is the concept of oppositely charged electrons and protons Matter s energy is scalar not vector any antimatter is a misconception including the concept of a positively charged electron and the idea of annihilation The Big Bang created four base particles proton p electron e neutrino and photon The electron usually shares energy with a photon as an electron unity e Electrons move to be dynamic unity expressed as two distinct types of oscillations 1 Electrons of an atom unity oscillate around their nucleus attracting while energy sharing Each electron s orbit is the equilibrium of its unity force 2 Outside electric forces can break free those outermost electrons from the atom unities of a conductor oscillate them away align and energize them forming stronger electron waves with magnetic effects and simultaneously cause them to flow along the potential difference as electric currents
Keywords: electron; mass; energy; unity; unity force; energy sharing; excess-energy releasing